Ethnic Christian Identity? The Case of Diogn. 1.1 - Chapa, Juan (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2019)
The ethnic character of early Christianity is a disputed subject. The reference to γένος at the beginning of the Letter to Diognetus is often mentioned in the debate to support a racial/ethnic understanding of Christian identity. For some scholars this interpretation would seem to be supported by the expression «third γένος/genus», which is found in Christian writers prior or contemporary to Diogn. The present paper advocates a non-ethnic interpretation of the term, by analysing the meaning of γένος in combination with ἐπιτήδευμα, the word that follows γένος and is united to it by ἢ. With examples taken from classical and Christian Greek literature, it is argued that for the author of Diogn. τοῦτο γένος ἢ ἐπιτήδευμα refers mainly to the way of life of Christians in the society in which they live, with no ethnic connotations.